2021
DOI: 10.3390/v13040655
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Serum Neutralization Assay: A Traditional Tool for a Brand-New Virus

Abstract: SARS-CoV-2 serum neutralization assay represents the gold standard for assessing antibody-mediated protection in naturally infected and vaccinated individuals. In the present study, 662 serum samples collected from February 2020 to January 2021 from acute and convalescent COVID-19 patients were tested to determine neutralizing antibody (NAb) titers using a microneutralization test (MNT) for live SARS-CoV-2. Moreover, anti-SARS-CoV-2 IgG, IgA, and IgM directed against different viral antigens were measured by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 41 publications
(60 reference statements)
2
32
1
Order By: Relevance
“…The ROC curve analysis indicated AUC=0.901(p<0.001), sensitivity 87.4%, and specificity 78.1%. It was much better than that reported by Matusali et al (Matusali et al, 2021).…”
Section: Verification Of Two Modelscontrasting
confidence: 51%
See 1 more Smart Citation
“…The ROC curve analysis indicated AUC=0.901(p<0.001), sensitivity 87.4%, and specificity 78.1%. It was much better than that reported by Matusali et al (Matusali et al, 2021).…”
Section: Verification Of Two Modelscontrasting
confidence: 51%
“…The protective capability of vaccine is another important subject concerned by people. Matusali et al reported that according to Italian guidelines, NAb titers ≥1:160 was a selection criterion for convalescent plasma for treating COVID-19 patients (Agenzia et al, 2021;Matusali et al, 2021;Peterhoff et al, 2021). It implies that people who got NAb titers ≥ 1:160 can be protected from SARS-CoV-2 infection.…”
Section: Verification Of Two Modelsmentioning
confidence: 99%
“…The June 2020 screening campaign evaluated the first epidemic outbreak, which affected our region between March and April 2020, thus allowing us to highlight the persistence of these antibodies over a period of at least a year, although pertinent serological follow-up could not be carried out for the entire period on more than eight residents due to the rest being vaccinated before M9. Similar timeframes have been described in the relevant scientific literature, with study follow-up ranging from 8 to 13 months (19)(20)(21). However, up until now, very few have focused on the elderly, who present with frailty, a high disease burden, and dependency.…”
Section: The Kinetics Of Neutralizing Sars-cov-2 Antibodiesmentioning
confidence: 66%
“…In our study, we investigated the value of different SARS-CoV-2 surrogate enzyme-linked immunosorbent assays (sELISAs) for the detection of neutralization-competent antibodies compared to a cell culture-based method (PRNT) and a quantitative anti-RBD spike IgG assay. The PRNT is one of the preferred methods to test anti-SARS-CoV-2 neutralization activity, but it is no longer regarded as the only “gold standard” [ 21 , 22 ]. In fact, also microneutralization assays and pseudovirus tests are widely accepted [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%